Stem Trait Spectra Underpin Multiple Functions of Temperate Tree Species - Yang, Shanshan; Sterck, Frank J.; Sass-Klaassen, Ute; Cornelissen, J. Hans C.; van Logtestijn, Richard S. P.; Hefting, Mariet; Goudzwaard, Leo; Zuo, Juan; Poorter, Lourens (Frontiers in Plant Science, 2022)
A central paradigm in comparative ecology is that species sort out along a slow-fast resource economy spectrum of plant strategies, but this has been rarely tested for a comprehensive set of stem traits and compartments. We tested how stem traits vary across wood and bark of temperate tree species, whether a slow-fast strategy spectrum exists, and what traits make up this plant strategy spectrum. For 14 temperate tree species, 20 anatomical, chemical and morphological traits belonging to six key stem functions were measured for three stem compartments (inner wood, outer wood and bark). Trait variation was explained by major taxa (38%), stem compartments (24%) and species within major taxa (19%). A continuous plant strategy gradient was found across and within taxa, running from hydraulic safe gymnosperms to conductive angiosperms. Both groups showed a second strategy gradient related to chemical defense. Gymnosperms strongly converged in their trait strategies because of their uniform tracheids. Angiosperms strongly diverged because of different vessel arrangement and tissue types. Bark had higher concentrations of nutrients and phenolics whereas wood had stronger physical defense. Gymnosperms have a conservative strategy associated with strong hydraulic safety and physical defense, and a narrow, specialized range of trait values, which allows them to grow well in drier and unproductive habitats. Angiosperm species show a wider trait variation in all stem compartments which makes them successful in marginal- and in mesic, productive habitats. Associations among multiple wood and bark traits collectively define a slow-fast stem strategy spectrum as is seen also for each stem compartment.